Chronic administration of the angiotensin type 2 receptor agonist C21 improves insulin sensitivity in C57BL/6 mice - Quiroga, Diego Tomás (2018)
The renin–angiotensin system modulates insulin action. Angiotensin type 1 receptor exerts a deleterious effect, whereas the angiotensin type 2 receptor (AT2R) appears to have beneficial effects providing protection against insulin resistance and type 2 diabetes. To further explore the role of the AT2R on insulin action and glucose homeostasis, in this study we administered C57Bl/6 mice with the synthetic agonist of the AT2R C21 for 12 weeks (1 mg/kg per day; ip). Vehicle-treated animals were used as control. Metabolic parameters, glucose, and insulin tolerance, in vivo insulin signaling in main insulin-target tissues as well as adipose tissue levels of adiponectin, and TNF-α were assessed. C21-treated animals displayed decreased glycemia together with unaltered insulinemia, increased insulin sensitivity, and increased glucose tolerance compared to nontreated controls. This was accompanied by a significant decrease in adipocytes size in epididymal adipose tissue and significant increases in both adiponectin and UCP-1 expression in this tissue. C21-treated mice showed an increase in both basal Akt and ERK1/2 phosphorylation levels in the liver, and increased insulin-stimulated Akt activation in adipose tissue. This positive modulation of insulin action induced by C21 appeared not to involve the insulin receptor. In C21-treated mice, adipose tissue and skeletal muscle became unresponsive to insulin in terms of ERK1/2 phosphorylation levels. Present data show that chronic pharmacological activation of AT2R with C21 increases insulin sensitivity in mice and indicate that the AT2R has a physiological role in the conservation of insulin action.